Development of a Shorinji Kempo training model based on local dances from East Nusa Tenggara to improve basic technical and affective skills of kenshi aged 9-12 years - Nyoman Wali, Carles; Riwu Kaho, Uly Jonathan (Jurnal Keolahragaan, 2025)
The integration of local cultural elements such as traditional dance into martial arts training offers a potential pathway to enhance both technical proficiency and affective learning among young practitioners. This study aimed to develop and test a feasible and practical Shorinji Kempo training model, based on local dances from East Nusa Tenggara (NTT), to improve basic techniques and affective aspects in kenshi aged 9–12 years. This study used a 10-step Borg and Gall research and development framework involved expert validation, small-scale trials (30 kenshi), and large-scale trials (100 kenshi) across five dojos in Yogyakarta. The subjects in this study were kenshi aged 9-12 years with a total of 130 kenshi. Data were collected through interviews, field notes, evaluation sheets, validation questionnaires, and a Kenshi assessment rubric. Three training models were developed: “Gotong Royong” (based on Lego-Lego dance), “Gembira” (Cakalele dance), and “Spirit” (Moko Nona dance). Results from expert validation showed high feasibility (100%). Paired t-test analysis revealed significant improvements in basic technical skills (p = 0.000) and affective aspects following the intervention. The intervention using the three training models resulted in an 87% improvement in basic technical skills and a 93% improvement in affective aspects among the kenshi. This study demonstrates that the Shorinji Kempo training model, grounded in the philosophical movements of East Nusa Tenggara traditional dances, effectively enhances both technical and affective competencies among young kenshi aged 9–12, offering a culturally grounded pedagogical approach that supports holistic development. The findings suggest that integrating local dance philosophies into martial arts training improves both motor and affective learning in young practitioners, providing an engaging and culturally relevant training alternative.